The Effects of Different Calcium Channel Blockers on Aldosterone-Producing Adenoma Cells - Wang, Fen; Ma, Xiaosen; Tong, Anli; Zhang, Yushi; Wen, Jin; Li, Yuxiu (Frontiers in Endocrinology, 2020)
The aim of this study is to examine the effects of different kinds of calcium channel blockers (CCBs) on primary aldosterone-producing adenoma (APA) mainly with KCNJ5 mutations. Primary cultured APA cells were treated with different calcium channel blockers (L/T type CCB benidipine, T-type CCB mibefradil and L-type CCB nifedipine), and aldosterone secretagogues with or without nifedipine. Aldosterone level, aldosterone synthase (CYP11B2) mRNA expression and cell proliferation were detected. The results showed that all three CCB’s significantly inhibit aldosterone secretion and CYP11B2 mRNA expression. Benidipine was relatively more effective than mibefradil or nifedipine. In addition, mibefradil only marginally inhibited cell proliferation. Adrenocorticotropin (ACTH) had a much stronger effect in stimulating aldosterone secretion and promoting cell proliferation from APA’s than angiotensin II (ATII). Different from ACTH and ATII, potassium had no effect. Nifedipine inhibited the basal and ACTH-, ATII-elicited aldosterone secretion. Twenty three of 24 APAs had somatic KCNJ5 mutation. In conclusion, benidipine, mibefradil and nifedipine significantly inhibit aldosterone secretion in primary cultured APA cells.